2017
DOI: 10.1039/c7cc04945e
|View full text |Cite
|
Sign up to set email alerts
|

Low-toxicity metallosomes for biomedical applications by self-assembly of organometallic metallosurfactants and phospholipids

Abstract: A new and convenient strategy for the preparation of metallosomes has been developed by mixing organometallic metallosurfactants and phospholipids. These aggregates show the characteristic properties of liposomes (stability upon dilution and low toxicity) and the toxicity is at least ten-fold lower than that of the metallosurfactant aggregates without phospholipids.The preparation and study of nanomaterials by self-assembly in aqueous medium is an increasingly relevant topic. Supramolecular structures for a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…It is apparent that despite the difference in the length and shape between both MTS and SPC, hydration of binary films allows the spontaneous formation of mixed aggregates. This fact parallels the behaviour of the mixtures of PCOL2 and TCOL2 with SPC, which also form aggregates, 17 even though the length of their hydrocarbon chains (2 methylene groups) is one-third those of PCOL6 and TCOL6. Thus, the known capacity of phospholipid fatty acid chains for filling (by rotation) the gaps generated inside the bilayers caused by the inclusion of short and bulky molecules should explain the formation of mixed vesicles.…”
Section: Structures Of the Mixed Aggregates Obtained By The Film Hydrmentioning
confidence: 67%
See 3 more Smart Citations
“…It is apparent that despite the difference in the length and shape between both MTS and SPC, hydration of binary films allows the spontaneous formation of mixed aggregates. This fact parallels the behaviour of the mixtures of PCOL2 and TCOL2 with SPC, which also form aggregates, 17 even though the length of their hydrocarbon chains (2 methylene groups) is one-third those of PCOL6 and TCOL6. Thus, the known capacity of phospholipid fatty acid chains for filling (by rotation) the gaps generated inside the bilayers caused by the inclusion of short and bulky molecules should explain the formation of mixed vesicles.…”
Section: Structures Of the Mixed Aggregates Obtained By The Film Hydrmentioning
confidence: 67%
“…Previous studies carried out with MTSs with shorter chains (2 carbon atoms, i.e., TCOL2 and PCOL2) demonstrated that they are stable in the dark, and that UVA and visible irradiations trigger CO release as gas. 17 This capability shows that, in fact, these molecules are photoCORMs, and that their different mixed aggregated structures can be used as drug (CO) delivery systems with potential biomedical applications.…”
Section: Structure Of the Mixed Aggregates Obtained By Microfluidicsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, we have chosen sodium triphenylphosphine trisulfonate (TPPTS) as a polar monodentate ligand. The bonding of both ligands [bidentate palmitoyl derivative (PD) and monodentate TPPTS] to a metal, as shown in Scheme , should lead to an amphiphilic complex (metallosurfactant), which is a potential candidate to be incorporated into the liposome bilayer. , Part of this work was previously presented as a poster…”
Section: Introductionmentioning
confidence: 99%